Filosofis Tradisi Madesa Adat di Desa Poh Bergong Kabupaten Buleleng (Kajian Nilai Keberagamaan) - I Made Sedana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The Madesa Adat marriage at a glance from the name and outward appearance looks the same as the famous marriage system in Bali, as previously mentioned, namely the Nyentana and Padegelahang marriage system or what is known as the Nyeburin marriage system. The method in this research is determining the location, type, approach, source and type, determining informants, instruments, collecting data by observation, interviews and document recording studies, analyzing data and presenting research results. The results in this study are a series of traditional madesa wedding ceremonies consisting of: (a) the traditional masadok stage, namely the party concerned in the traditional house discussing the implementation of the marriage, (b) the piuning stage at the village temple, namely the stage where the party concerned will notify the marriage ceremony, (c) the stage of implementing the marriage consists of reporting the sign, confirming, taking it to the top of the event.